Identification of polycomb repressive complex 1 and 2 core components in hexaploid bread wheat - Strejčková, Beáta; Čegan, Radim; Pecinka, Ales; Milec, Zbyněk; Šafář, Jan (BMC plant biology, 2020)
BACKGROUND: Polycomb repressive complexes 1 and 2 play important roles in epigenetic gene regulation by posttranslationally modifying specific histone residues. Polycomb repressive complex 2 is responsible for the trimethylation of lysine 27 on histone H3; Polycomb repressive complex 1 catalyzes the monoubiquitination of histone H2A at lysine 119. Both complexes have been thoroughly studied in Arabidopsis, but the evolution of polycomb group gene families in monocots, particularly those with complex allopolyploid origins, is unknown. RESULTS: Here, we present the in silico identification of the Polycomb repressive complex 1 and 2 (PRC2, PRC1) subunits in allohexaploid bread wheat, the reconstruction of their evolutionary history and a transcriptional analysis over a series of 33 developmental stages. We identified four main subunits of PRC2 [E(z), Su(z), FIE and MSI] and three main subunits of PRC1 (Pc, Psc and Sce) and determined their chromosomal locations. We found that most of the genes coding for subunit proteins are present as paralogs in bread wheat. Using bread wheat RNA-seq data from different tissues and developmental stages throughout plant ontogenesis revealed variable transcriptional activity for individual paralogs. Phylogenetic analysis showed a high level of protein conservation among temperate cereals. CONCLUSIONS: The identification and chromosomal location of the Polycomb repressive complex 1 and 2 core components in bread wheat may enable a deeper understanding of developmental processes, including vernalization, in commonly grown winter wheat.
Keywords: Triticum; PRC1; PRC2; počítačová simulace; mapování chromozomů; sekvenování transkriptomu; Chromosome Mapping; Epigenetics; Chromosomes, Plant; chromozomy rostlin; Evolution, Molecular; RNA rostlin; molekulární evoluce; stanovení celkové genové exprese; Computer Simulation; Phylogeny; RNA, Plant; Histone methylation; Polycomb repressive complex; Wheat; Polycomb Repressive Complex 2; RNA-Seq; pšenice; fylogeneze; Polycomb Repressive Complex 1; Gene Expression Profiling